(untitled) (Acta Entomológica Chilena, 2022)
The following new species from northernmost Chile are described: Notogramma azapae, Ceroxys friasi (paratype also from Perú), and C. pallidus. A key to the American species of Ceroxys, including also the Palearctic type of the genus, C. urticae (L.), is given. Ceroxys is considered in a broad sense, including Pterotaenia Rondani, Pseudomelieria Bréthes, and Platyeuxesta Blanchard, with several new combinations with Ceroxys made in the key.